the Infak Persenan ISRUN Lembaga Dakwah Islam Indonesia Perspective of Fatwa of Majelis Tarjih Muhammadiyah - Laseri, Tanto Fatkhurrozi; Sindy Marchelia Putri; Bakhrul Huda (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2024)
Tujuan – The purpose of this study is to examine the infaq sedekah routine (ISRUN) at Lembaga Dakwah IslamIndonesia (LDII) organisation in the perspective of the fatwa of the Majelis Tarjih Muhammadiyah. Metode – This research uses library research method with descriptive research type. The data sources in this research are data from documents, books, internet journals and references related to ISRUN of LDII mass organisation.. Hasil Penelitian The result of this research is that in giving infaq, both LDII and the fatwa of Majelis Tarjih Muhammadiyah view infaq as an integral part of Islamic religious practice. the difference lies in the approach and implementation and regulation of the practice of infaq. LDII requires isrun as part of religious practices that must be followed, while the Majelis Tarjih emphasises the principle of freedom and voluntarism in giving without binding a certain amount or percentage. Keterbatasan – This research has shortcomings in the lack of sources from previous research that discusses LDII's gratuity infaq so that the sources taken from previous research are not much found. This research combines the fatwas of Islamic mass organisations in Indonesia which have differences in terms of views on worship, especially infaq and alms. Implikasi Praktis – As a practical implication, the results of this study can be used as a reference by community organisations in Indonesia to determine the laws and policies of infaq, of course, differences are a natural thing so that it can be used as knowledge for readers to find